Promotion Strategies for Social Marketing for Utilization in the Creation of Health Promotion Awareness Programs: Case Study of Nottinghamshire, United Kingdom - Saboor, Abdul; Taj, Imtiaz; Abbasi, Rashid Shabir; Rehman, Abdul (Asosiasi Ahli Administrasi Indonesia, 2024)
The worksite health promotion program addresses empirical research to bring decreased healthcare cost of the organization and improve overall flexibility of employees in following a healthy lifestyle. Thus, the interventions have to be planned and marketed in such a way that the detrimental impact generated because of an unfit labor force can be avoided. This study seeks to find out to what extent program coordinators will consider the social marketing promotional strategies in organizations in Nottinghamshire, United Kingdom. The data is collected from the 60 program controllers using the structured study. These findings thus showed that at least one of the four social media marketing techniques used (publicity, sales promotion, public relations, and advertising) was used by these program coordinators. Further, it is found that most of those coordinators of the program were not given training with social media marketing promotional strategies. However, usage of promotional strategy in the two different types of business has no noticeable gap. The result has though therefore suggested that facilitated training program to the program coordinators is necessary so that meaningful results can be achieved.